Reducing visual analog scale (VAS) in circumcision patient by the additional of topical anesthesia agent in local anesthesia procedures - M. Fadel Dikaprio; Romdhoni, Muhammad Fadhol; Riyanto, Refni Riyanto; Susiyadi (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
Circumcision could be painful before, during, and after the surgery. The local anesthesia is often used in medical practice in order to reduce pain during circumcision. Topical anesthesia works by eliminating pain sensation after direct application on skin. This study aimed to investigate the effect of additional of topical anesthesia agent for circumcision on the visual analog scale (VAS). It was a cross sectional study using the data of medical records from a Circumcision Clinic (Rumah Sunatan) in Purwokerto, Central Java conducted from July 2019 to March 2020. As a result, there were 127 subjects (70.6%) belong to Mild Category VAS, while 26 subjects (14.4%) got Moderate, and 27 subjects (15.0%) fall under Severe Category. The application of topical anesthesia for circumcision could reduce the VAS value by 70.6 %.